2013
DOI: 10.1556/eujmi.3.2013.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of essential oils and chloroform alone and combinated with cetrimide againstEnterococcus faecalisbiofilm

Abstract: The Enterococcus faecalis bacteria have been identified as the most commonly recovered species from teeth with persistent endodontic infections. The antimicrobial activity of essential oils and chloroform (CHL), alone and in association with various concentrations of cetrimide (CTR), against biofilm of Enterococcus faecalis was investigated. Solutions of CHL, eucalyptus oil (EO) and orange oil (OO) associated with CTR at 0.3%, 0.2%, 0.1%, and 0.05% were used to determine antimicrobial activity by exposing trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…Biological activity of many pytocompounds is based on cell membrane permeabilization. Such a process occuring in microorganisms leads to a loss of ions, leakage of macromolecules, reduction of membrane potential and fluidity, decrease in the ATP pool, and finally to osmotic lysis and microbial death (Alviano & Alviano, 2009;Bakkali et al, 2008;Cushnie & Lamb, 2005;2011;Martos et al, 2013;McMahon et al, 2007). Antimicrobial activity of phytocompounds may also derive from their pro-oxidative properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological activity of many pytocompounds is based on cell membrane permeabilization. Such a process occuring in microorganisms leads to a loss of ions, leakage of macromolecules, reduction of membrane potential and fluidity, decrease in the ATP pool, and finally to osmotic lysis and microbial death (Alviano & Alviano, 2009;Bakkali et al, 2008;Cushnie & Lamb, 2005;2011;Martos et al, 2013;McMahon et al, 2007). Antimicrobial activity of phytocompounds may also derive from their pro-oxidative properties.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, polyphenols (with the largest and the best known group of flavonoids) and essential oils are the most promising. Important advantages of most of the natural products include their wide-spectrum of activity and effectiveness irrespective of the drug susceptibility of target microorganisms, demonstrating at the same time an extremely low risk of giving rise to resistance mechanisms (Bakkali et al, 2008;Budzyńska et al, 2011;Chaieb et al, 2011;Cushnie & Lamb, 2005;2011;Fankam et al, 2011;Martos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…All remaining bone cubes (30 cranial and 37 caudal) were found to be fully remodeled (i.e. their entire transverse surface revealed Haversian systems with no evidence of primary plexiform bone) and they were stored in 1.5 ml Eppendorf tubes containing paper soaked in saline solution with 8% chloroform to prevent bacterial growth (Martos et al, 2013). Samples were kept frozen at −20°C until mechanical testing.…”
Section: Cortical Cubes Preparationmentioning
confidence: 99%
“…However, literature is scarce regarding studies that evaluated antimicrobial activity of these isolated phytoconstituents against E. faecalis. Some authors [8,9,[22][23][24][25] The experimental root canal filling paste composed by combined phytoconstituents showed a better antibacterial effect than the one consisted of only terpineol. Previous studies have shown a synergism between terpineol and cinnamaldehyde when interacting with other essential oil components [27,29].…”
Section: Discussionmentioning
confidence: 99%